A7.14 IRF5 Polymorphisms in Systemic Sclerosis. (25th February 2013) - Stock, C; Sato, H; Fonseca, C; Wells, AU; Denton, CP; Abraham, DJ; Lindahl, G; Renzoni, EA
Abstract : Introduction: The transcription factor interferon regulatory factor 5 (IRF-5) plays a key role in the Toll-like receptor signalling pathway, and activation of the type I interferon response. As well as being associated with a number of other rheumatological diseases, including systemic lupus erythematosus and rheumatoid arthritis, IRF5 has been identified as a candidate gene for systemic sclerosis (SSc) in a number of genome wide association studies. Although this finding has been replicated in several different studies, there has been variation in the single nucleotide polymorphisms (SNPs) tested, thereby making it difficult to determine which IRF5 SNP(s) may be playing a role in susceptibility to SSc. We therefore tested a number of IRF5 SNPs in a UK based population with the aim of elucidating the true causal variant(s). Materials and Methods: To investigate involvement of this gene in susceptibility to SSc, UK Caucasian patients and controls (SSc n = 465, controls n = 416) were genotyped using commercially available TaqMan assays. The IRF5 SNPs Rs4728142, Rs2004640, Rs10954213, and Rs10488631, previously reported to be associated with SSc, were selected for investigation. The presence of pulmonary fibrosis was defined as a forced vital capacity <75% and/or the presence of fibrosis on chest imaging. Results: The allele frequencies of each of the four IRF5 SNPs were not significantly different (using Bonferroni correction for multiple testing) in the healthy controls and patients with SSc (Rs4728142: 0.52/0.50, Rs2004640: 0.56/0.60, Rs10954213: 0.37/0.35, Rs10488631: 0.12/0.14). There was also no significant difference found for any of the SNPs when the SSc patients were subdivided according to disease type (limited/diffuse), presence of pulmonary fibrosis, or auto-antibody type. Conclusions: In contrast to previously published studies we did not detect a significant difference in allele frequency between patients with SSc and healthy control individuals for any of the four IRF5 SNPs tested. However, due to the modest cohort sizes available, this study has limited power and therefore may have been unable to detect allele frequency differences with small effects. This study therefore will be repeated with larger cohorts in order to validate these results.